Successful treatment of a premature newborn with isolated gastric perforation - I. H. Shidakov (Вестник хирургии имени И.И. Грекова, 2020)
In the Republican perinatal center, there was a premature newborn girl who had a combination of various risk factors in the antenatal and postnatal period. From birth, the child was in the intensive care unit, required intensive care. Against the backdrop of positive dynamics, at the 4th week of life, the child’s condition worsened noticeably, signs of pneumoperitoneum appeared. After emergency laparocentesis, it took several days to stabilize the condition. Laparotomy was performed in a deferred order, in which isolated perforation of the posterior wall of the stomach was detected. The scope of the operation was limited to suturing the opening, since no other changes from the small and large intestine were detected. In the postoperative period, the child’s condition remained severe for a long time, was in the neonatal intensive care unit. The child was discharged home with recovery after 3 months.